Microrobots Derived from Variety Plant Pollen Grains for Efficient Environmental Clean Up and as an Anti‐Cancer Drug Carrier. (13th March 2020) - Maric, Tijana; Nasir, Muhammad Zafir Mohamad; Rosli, Nur Farhanah; Budanović, Maja; Webster, Richard D.; Cho, Nam‐Joon; Pumera, Martin
Abstract: The production of large quantities of micromachines and microrobots is limited by fabrication methods and the use of synthetic templates. Pollen is one of the most stable structures in the world, capable of surviving harsh treatment and for millions of years. Pollen grains are available in large variety of shapes and sizes. The use of a wide variety of naturally abundant, nontoxic pollen grains for the efficient fabrication of platinum‐pollen (Pt‐pollen) hybrid microrobots capable of fast propulsion for environmental and biomedical applications is demonstrated. Nine different pollen grains are selected and modified (dandelion, pine, lotus, sunflower, poppy, camellia, lycopodium, cattail, and galla) to demonstrate the robustness of different types of pollen grains for potential applications in environmental remediation. The efficient mobility rendered by the fabricated microrobots enhances their performance in the removal of heavy metals in aqueous medium. Furthermore, they can be used as doxorubicin carriers. Abstract : Nine different naturally abundant and nontoxic pollen grains (dandelion, pine, lotus, sunflower, poppy, camellia, lycopodium, cattail, and galla) are selected and modified for the fabrication of microrobots. These microrobots are capable of fast propulsion and have enhanced environmental‐remediation performance. These microrobots can also be used as doxorubicin carriers.